PSYCHOLOGICAL PECULIARITIES OF PROFESSIONAL RESPONSIBILITY OF FUTURE SPECIALISTS OF THE CIVIL DEFENCE SERVICE - Mokhnar L. I.; Fomych M. V.; Diachkova O. M.; Kryshtal M. A. (International Journal of Innovative Technologies in Social Science, 2020)
The essence of the concept of “responsibility” and “professional responsibility of a rescuer” is revealed in the article; the psychological foundations of the development of responsible behavior are analyzed; the main ways and means that ensure the success of the process of the responsibility formation, the main pedagogical conditions for improving educational activities and the formation of responsibility among the cadets are presented.